Circadian influence on inflammatory response during cardiovascular disease. (April 2021) - Aziz, Iman S.; McMahon, Adam M.; Friedman, David; Rabinovich-Nikitin, Inna; Kirshenbaum, Lorrie A.; Martino, Tami A.
Abstract: Circadian rhythms follow a 24 h day and night cycle, regulate vital physiological processes, and are especially relevant to cardiovascular growth, renewal, repair, and remodeling. A recent flurry of clinical and experimental studies reveals a profound circadian influence on immune responses in cardiovascular disease. The first section of this review summarizes the importance of circadian rhythms for cardiovascular health and disease. The second section introduces the circadian nature of inflammatory responses. The third section combines these to elucidate a new role for the circadian system, influencing inflammation in heart disease, especially myocardial infarction. Particular focus is on circadian regulation of the NACHT, LRR, and PYD domains–containing protein 3 inflammasome, neutrophils, monocytes/macrophages, and T cells involved in cardiac repair. A role for biological sex is noted. The final section explores circadian influences on inflammation in other major cardiovascular conditions. Circadian regulation of inflammation has profound implications for benefitting the diagnosis, treatment, and prognosis of patients with cardiovascular disease.